Inter-Municipal Cooperation in Waste Management: The Case of Poland - Kołsut, Bartłomiej (Quaestiones Geographicae, 2016)
This article seeks to present the scale of inter-municipal cooperation in waste management in Poland in the light of the role of three key factors of cooperation. The first shows spatial regularities in the distribution of inter-municipal bodies involved in waste management in Poland, both in the system of voivodeships and historical-cultural regions. The second is institutional conditions confirming the scale of the Europeanisation of public policies taking place in Poland. It embraces the implementation of the EU legal framework in the Polish legal system and the cooperative behaviour of municipalities as a result of those changes. The third is a negative verification of the assumptions of the economic theory upholding the role of financial motivation in establishing cooperation (looking for savings and economies of scale to reduce unit cost); the presented results do not corroborate this type of motivation.